Lymphoma B cells remodel bone marrow stromal cells into extracellular matrix–producing cancer-associated fibroblasts - Elise Dessauge; Baptiste Brauge; Simon Léonard; Alicia Beyou; Camille Laurent; Valentin Isen; Nicolas Barbier; Céline Monvoisin; Thomas Lejeune; Jérôme Destin; Florence Jouan; Judikael Saout; et al. (Blood Advances, 2025)
Abstract: Bone marrow (BM) involvement is a common feature of germinal center–derived B-cell lymphomas and is associated with a poor prognosis. In particular, follicular lymphoma (FL) infiltrates the BM in 70% of cases, and analysis of in vitro–expanded FL BM mesenchymal stromal cells (MSCs) has revealed an extensive alteration of BM stromal cell phenotypic, transcriptomic, and functional profiles. However, the mechanisms underlying the direct interplay between lymphoma B cells and their permissive stromal niche in situ have not yet been identified. In this study, we identified a significant remodeling of extracellular matrix (ECM) composition and organization in the BM of patients with FL and in a murine model of lymphoma B-cell BM xenograft. In particular, murine leptin receptor (LepR+) MSCs were identified by single-cell RNA sequencing as engaged in a bidirectional cross talk with malignant B cells, triggering their specific and progressive reprogramming and commitment toward a phenotype resembling that of human ECM/transforming growth factor β (TGFβ) myofibroblastic cancer–associated fibroblasts (CAFs) and FL-CAFs. Kinetic analysis of FL BM samples showed that ECM and TGFβ deregulation persisted after treatment, suggesting it may contribute to disease persistence and relapse. Overall, this work sheds new light on the kinetics and mechanisms of BM stromal niche reshaping in B-cell lymphomas.